Evaluación de dos híbridos de pimiento (Capsicum annuum L.), cultivados en sistema hidropónico en sustratos y soluciones nutritivas - Amores Bravo, Borislao Augusto (2017)
SUMMARY During the dry season of 2017 the present study was carried out in the Experimental Farm "San Pablo" of the Technical University of Babahoyo. The objectives were: 1) To evaluate the performance of the "Marcato F1" and "Cortes F1" hybrids under the hydroponic system of solid substrate, 2) Determine the level of nutritive solutions that maximizes pepper yield, and 3) Carry out a economic analysis. Six treatments were formulated that combined two hybrids and three solutions with a growing nutrient concentration, plus two control treatments with conventional fertilization (140 Kg. N. + 65 Kg. P. + 190 Kg. K. per hectare) on firm ground, all the plots were established in the open field. The experimental design of randomized complete blocks (BCA) with factorial arrangement 2 x 3 + 2 in three repetitions was used and to determine the statistical differences between the means of the treatments the Duncan Multiple Range test was used at 95% probability. . The variables studied were plant height at 30, 45 and 60 days after the transplant, days to flowering, number of fruits per plant, length, diameter and weight of fruits, foliar analysis at the beginning of flowering and yield. The plants cultivated under the hydroponic system presented an anticipated flowering compared to the controls; the foliar analysis showed that in the treatments T2, T3, T6 and T7 (medium and low doses) the nitrogen level (2.39% - 2.95%) was below the adequate level (3.0% - 4, 5%), which affected the height of the plants, fruits per plant and yield / ha. The more concentrated nutrient solution made the Marcato hybrid the highest yield with a net income of $ 6325 per hectare compared to $ 2383.27 for the control. The production costs were $ 2087.47 and $ 1901.78 in the same order for this hybrid.